PEMANFAATAN ALOKASI DANA DESA DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT DESA BATU PUTIH DAYA - Badrissyamsi Habiburrahman; ida Nuraini (Program Studi Ekonomi Pembangunan, 2019)
The purpose of this study was to determine the benefits felt by the people of Batu Putih Daya Village with the Village Funds in Batu Putih Daya Village, Batu Putih District, Sumenep Regency, East Java Province, and to find out the opinion of the Batu Putih Daya community regarding the utilization of the Village Fund in Batu Putih Daya Village. This study uses primary data taken through a questionnaire to village heads and communities in Batu Putih Daya Village. Data analysis method used in this research is descriptive analysis. The results showed that the utilization of the Village Fund allocation in Batu Putih Daya Village was used in several aspects, namely the aspects of religion, health, education, economy and infrastructure. Furthermore, some of the benefits felt directly by the community with the Village Fund in Batu Putih Daya Village are ease of transportation because the road has been improved, ease of water sources for agriculture with the wellbore program provided in each hamlet and the aid of tools in the form of machines to mine white stones able to facilitate the activities of white stone miners. Then in general the people in Batu Putih Daya Village considered that the Village Fund was not providing benefits, this was because the Village Fund had not been able to improve the economy of the people in Batu Putih Daya Village.